Prenatal bisphenol A and birth outcomes: MOCEH (Mothers and Children's Environmental Health) study - Lee, Bo-Eun; Park, Hyesook; Hong, Yun-Chul; Ha, Mina; Kim, Yangho; Chang, Namsoo; Kim, Boong-Nyun; Kim, Young Ju; Yu, Seung-Do; Ha, Eun-Hee (International journal of hygiene and environmental health, 2014)
Bisphenol A (BPA) is used primarily in the production of polycarbonate plastics and epoxy resins. Widespread exposure to BPA has created a great deal of concern regarding its potential adverse effects on human health. This study examined the relationship between prenatal BPA exposure and birth outcomes, including birth weight, birth length, and ponderal index considering gender difference. A multi-center birth cohort study, Mothers and Children's Environmental Health (MOCEH) has been established in Korea since 2006. Study subjects are 757 pregnant women from the original cohort, who had their urinary BPA level measured during the third trimester, as well as information on birth outcome, prior medical history, psychosocial status, health behavior, environmental exposure as well as socio-demographic characteristics. Regression analysis was performed to assess the effect of BPA on birth outcome. The geometric mean concentration of BPA in pregnant women was 1.29μg/L (1.87μg/g creatinine) during late pregnancy. Urinary BPA concentrations were shown to be higher in women with a higher income level. Univariate regression analysis revealed a significant association between BPA levels and birth weight. In adjusted analysis, the second tertile of maternal BPA exposure exhibited an increase in birth weight, relative to the first tertile (p=0.04). These relationships were more pronounced in male neonates. Also, prenatal exposure to BPA was associated with an increase of ponderal index in total, and especially female neonates. This study shows that the association of prenatal exposure to BPA with anthropometric measures, such as birth weight and birth length, differed by gender. Further study is required to more fully elaborate this relationship between prenatal BPA exposure and birth outcome.